Click and Release: A Chemical Strategy toward Developing Gasotransmitter Prodrugs by Using an Intramolecular Diels–Alder Reaction. (23rd November 2016) - Ji, Xingyue; Zhou, Cheng; Ji, Kaili; Aghoghovbia, Robert E.; Pan, Zhixiang; Chittavong, Vayou; Ke, Bowen; Wang, Binghe
Abstract: Prodrug strategies have been proven to be a very effective way of addressing delivery problems. Much of the chemistry in prodrug development relies on the ability to mask an appropriate functional group, which can be removed under appropriate conditions. However, developing organic prodrugs of gasotransmitters represent unique challenges. This is especially true with carbon monoxide, which does not have an easy "handle" for bioreversible derivatization. By taking advantage of an intramolecular Diels–Alder reaction, we have developed a prodrug strategy for preparations of organic CO prodrugs that are stable during synthesis and storage, and yet readily release CO with tunable release rates under near physiological conditions. The effectiveness of the CO prodrug system in delivering a sufficient quantity of CO for possible therapeutic applications has been studied using a cell culture anti‐inflammatory assay and a colitis animal model. These studies fully demonstrate the proof of concept, and lay a strong foundation for further medicinal chemistry work in developing organic CO prodrugs.